The Therapeutic Potential of Baicalin and Baicalein in Breast Cancer: A Systematic Review of Mechanisms and Efficacy - Bartłomiej Zieniuk; Şuheda Uğur (Current Issues in Molecular Biology)
Cancer remains a leading cause of death globally, with breast cancer being the most commonly diagnosed cancer in women. This systematic review focuses on the therapeutic potential of baicalin and baicalein, two bioactive flavonoids derived from Scutellaria baicalensis, in breast cancer treatment. These compounds exhibit anticancer properties through mechanisms such as apoptosis induction, cell cycle arrest, and inhibition of metastasis. Baicalin and baicalein modulate key signaling pathways, including NF-κB, PI3K/AKT/mTOR, and Wnt/β-catenin, and have shown efficacy in both in vitro and in vivo models. Their synergy with chemotherapy agents and incorporation into nanotechnology-based delivery systems highlight opportunities to enhance therapeutic outcomes. However, current evidence is predominantly preclinical, with limited clinical trials to validate their safety and efficacy in humans. Challenges such as poor bioavailability and rapid metabolism also underscore the need for advanced formulation strategies. This review synthesizes current evidence on the molecular mechanisms, therapeutic efficacy, and potential applications of baicalin and baicalein in breast cancer research.